A Comprehensive Review of Biological Agents for Lupus: Beyond Single Target - Yang, Bingyi; Zhao, Ming; Wu, Haijing; Lu, Qianjin (Frontiers in Immunology, 2020)
Systemic lupus erythematosus (SLE) is an autoimmune disease that involves multiple immune cells. Due to its complex pathogenesis, the effectiveness of traditional treatment methods is limited. Many patients have developed resistance to conventional treatment or are not sensitive to steroid and immunosuppressant therapy, and so emerging therapeutic antibodies have become an alternative and have been shown to work well in many patients with moderate and severe SLE. This review summarizes the biological agents that are in the preclinical and clinical trial study of SLE. In addition to the various monoclonal antibodies that have been studied for a long time, such as belimumab and rituximab, we focused on another treatment for SLE, bispecific antibodies (BsAbs) such as tibulizumab, which simultaneously targets multiple pathogenic cytokines or pathways. Although the application of BsAbs in cancer has been intensively studied, their application in autoimmune diseases is still in the infant stage. This unique combined mechanism of action may provide a novel therapeutic strategy for SLE.